Retinoblastoma Protein Paralogs and Tumor Suppression - Flores, Mauricio; Goodrich, David W. (Frontiers in Genetics, 2022)
The retinoblastoma susceptibility gene (RB1) is the first tumor suppressor gene discovered and a prototype for understanding regulatory networks that function in opposition to oncogenic stimuli. More than three decades of research has firmly established a widespread and prominent role for RB1 in human cancer. Yet, this gene encodes but one of three structurally and functionally related proteins that comprise the pocket protein family. A central question in the field is whether the additional genes in this family, RBL1 and RBL2, are important tumor suppressor genes. If so, how does their tumor suppressor activity overlap or differ from RB1. Here we revisit these questions by reviewing relevant data from human cancer genome sequencing studies that has been rapidly accumulating in recent years as well as pertinent functional studies in genetically engineered mice. We conclude that RBL1 and RBL2 do have important tumor suppressor activity in some contexts, but RB1 remains the dominant tumor suppressor in the family. Given their similarities, we speculate on why RB1 tumor suppressor activity is unique.